Pengaruh tingkat suku bunga SBI terhadap nilai tukar rupiah studi pada Bank Indonesia - Melinda Puspita Ayu Kirana (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2017)
This study describes the influence of SBI interest rate on the rupiah at Bank Indonesia studies. The method in this research is descriptive method with quantitative approach. Determination of the sample is based on time series data 2009-2015 period by using saturation sampling methods as many as 84 samples. This research was conducted at Bank Indonesia has the sole purpose of achieving and maintaining stability in the rupiah. This study uses simple linear regression analysis which includes the classical assumption and hypothesis testing in the form of the coefficient of determination (r2) and the partial test (t test). The results showed that the interest rate significantly influence the exchange rate. This is shown by the results of the t test T_hitung amounted to 9.745, while T_ (table) amounted to1,989. This means T_ (count) > T_tabel (9.745 > 1.989) it can be concluded that the null hypothesis is rejected and the alternative hypothesis is accepted.